Background minimisation of HPGe detector by passive graded shielding. (18th April 2012) - Singh, Vishwanath P.; Veerendra, D.D.; Dileep, B.N.; Sheikh, Q.; Managanvi, S.S.; Badiger, N.M.; Bhat, H.R.
A simple and economical passive graded shielding which is combination of low and high Z materials for HPGe detector for background radiation minimisation is developed for better identification of the peaks in acquired spectrum by reducing Compton continuum. The present paper discusses the design and advantages of the passive graded shielding (lead + copper + aluminium) which encloses the HPGe detector. The passive graded shielding improved sensitivity of the detector and reduced Minimum Detectable Activity (MDA) for planchet source from 19.6% to 11.7% for gamma photon energies in the range of 81–1408 keV and brought down the MDA, 35.25 GBq d –1 and 35.26 GBq d –1 for 133 Xe and 135 Xe respectively which was 72.31 GBq d –1 and 78.27 GBq d –1 for noble gases in gaseous effluents before shielding of the detector. The passive graded shielding as integral part is considerably very useful for radiological protection at nuclear power/research reactors by minimising background radiation.